PERBANDINGAN KINERJA KEUANGAN PT GUDANG GARAM Tbk DENGAN PT HM SAMPOERNA Tbk BERDASARKAN ANALISIS ECONOMIC VALUE ADDED - Berlianti, Anista -; -, Sunarso - (Universitas Slamet Riyadi, 2013)
ABSTRACT The purpose of this study is to analyze the financial performance of PT Gudang Garam Tbk and PT HM Sampoerna Tbk if measured using economic value added analysis and comparison to analyze the financial performance of PT Gudang Garam Tbk and PT HM Sampoerna Tbk if measured using value added economic analysis. The data used is the qualitative and quantitative data and data sources used are secondary data. Analyzed using economic value of research added. Economic value added analysis that the financial performance of PT Gudang Garam Tbk is good. During a period of three years (2009 - 2011) there is an increase in financial performance. In addition, the financial performance of PT HM Sampoerna Tbk within a period of 3 years is also good. However, after the financial performance of the company compared the results of both studies suggest that the financial performance of PT HM Sampoerna Tbk better than PT Gudang Garam Tbk. Keywords: Financial performance, Economic Value Added, PT Gudang Garam Tbk, PT HM Sampoerna Tbk.